Pengaruh Kualitas Layanan terhadap Kepuasan Mahasiswa Program Pascasarjana Magister Manajemen STIE ABI Surabaya: The Effect of Service Quality on Student Satisfaction in the Postgraduate Master of Management Program STIE ABI Surabaya - Kusdiyantoro, Sujadi (Universitas Muhammadiyah Sidoarjo, 2014)
This research do the analysis afterwards several factors that can affect satisfaction students graduate program management abi magister stie surabaya .Research objectives of research is to be accomplished: (1) to know the quality of services the influence of factors which consists of physical proof (tangible), keterandalan (reliability), responsiveness (responsiveness), and guarantee (assurance) and simultaneous partial evaluation as well as the most dominant against satisfaction students graduate program management abi magister stie surabaya .The population in this research was all students graduate program management abi magister stie surabaya as many as 145 people.The size of the sample determined as many as 100 percent of the population the size of the total sample so that in this research was as many as 145 people out by a total of sampling technique or the sampling method of saturated .To research is used model double linear regression analysis . Conclusion in this research is as follows: (1) factors the quality of services which consists of physical proof (tangible), keterandalan (reliability), responsiveness (responsiveness), and guarantee (assurance) in unison have leverage significantly to satisfaction students graduate program management abi magister STIE Surabaya, (2) all the factors the quality of services which consists of physical proof (tangible), reliability, responsiveness (responsiveness), and guarantee (assurance) partial evaluation that are meaningful satisfaction have leverage against students graduate program management abi magister stie surabaya, (3) factors that have a dominant influence on student satisfaction graduate program management abi magister stie surabaya is the guarantee (assurance).